Legal Protection for Buyers of Mortgage Rights Execution Auctions in the Case of Blocking the Certificate of Ownership which becomes the Object of the Auction - Dian Pratiwi, Rizky Melani; Widhiyanti, Hanif Nur; Wisnuwardhani, Diah Aju (Batulis Civil Law Review, 2023)
Introduction: Article 45 paragraph 1 letter e creates legal uncertainty regarding the rights of the auction winner in terms of transfer of rights and control of the auction object due to a blockade from the debtor or other party.Purposes of the Research: The purpose of this research is to examine the legal certainty of Article 45 Paragraph 1 Letter e of Government Regulation No. 24 of 1997 concerning Land Registration against blocking of auction objects and legal protection for auction winners executing mortgage rights in the event of blocking of auction objects.Methods of the Research: The research method used is normative legal research.Results of the Research: The results of the study show that the form of legal protection for the auction winner is preventive legal protection, in which the name transfer process by the auction winner should still be carried out by understanding the meaning of Article 45 paragraph 1 lettere, namely the material claim or dispute referred to is limited to ownership disputes, not debts. Furthermore, legal protection is repressive, i.e. the auction winner can request assistance from the District Court to empty the object. The auction winner can hold the seller accountable in the form of compensation, and the auction winner can file a lawsuit against the unlawful act against the blockade applicant and the Land Office as the institution authorized to carry out block records.